2013
DOI: 10.1185/03007995.2013.815158
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Medical Research Ethics Committee (MREC), National Research Center of Egypt, 2003–2011

Abstract: Since 2005, the MREC in NRC Egypt has built up considerable experience of evaluating the ethical issues arising within the field of medical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…An investigator’s need to make considerable revisions to a protocol can delay the Committee’s review process and create hurdles that investigators may inappropriately blame on the Committee [ 20 ]. Our findings comport with several studies that have shown that ethical and procedural issues are the primary reasons for RECs’ non-approval of protocols after first review [ 18 , 21 , 22 ]. Similar to these studies, we found that many applications not approved in the first review had issues that included violations of procedures, missing information, and discrepancies between different parts of the application, as well as grammatical and spelling errors [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…An investigator’s need to make considerable revisions to a protocol can delay the Committee’s review process and create hurdles that investigators may inappropriately blame on the Committee [ 20 ]. Our findings comport with several studies that have shown that ethical and procedural issues are the primary reasons for RECs’ non-approval of protocols after first review [ 18 , 21 , 22 ]. Similar to these studies, we found that many applications not approved in the first review had issues that included violations of procedures, missing information, and discrepancies between different parts of the application, as well as grammatical and spelling errors [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…In 4 studies, female membership was underrepresented (Ikingura et al, 2007; Matar & Silverman, 2013; Moodley & Myer, 2007; Nyika, Kilama, Chilengi, et al, 2009). Notably, 1 REC in Egypt reported more (10 of 17) female than male members (Abdel-Aal, Ghaffar, & El Shabrawy, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies assessed training needs of RECs and reported that the majority of committee members needed more ethics training (Abdel-Aal et al, 2013; Ateudjieu et al, 2010; IJsselmuiden et al, 2012; Ikingura et al, 2007; Kass et al, 2007; Matar & Silverman, 2013; Milford et al, 2006; Moodley & Myer, 2007; Nyika, Kilama, Chilengi, et al, 2009; Oyedeji, 2011; Sleem et al, 2010). Two studies reported that REC members expressed a need for more training on evaluation of scientific design and determination of risks in clinical trials (Milford et al, 2006; Nyika, Kilama, Chilengi, et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The human medical research ethics committees are referred to as either Institutional Review Board (IRB) or Research Ethics Committee (REC). Some of the RECs may approve animal research protocols when needed such as the Medical Research Ethics Committee (MREC) of the National Research Center (NRC) [1]. Cairo University has been the incubator and disseminator of knowledge and culture in Egypt and the neighboring countries for the last century.…”
Section: Introductionmentioning
confidence: 99%